Taḥlīl al-Akhtā’ al-Naḥwiyyah fī Qirā’ah al-Nuṣūṣ al-‘Arabiyyah li al-Ṭālibāt al-Ma‘Had fī al-Marḥalah al-Mutawassiṭah - Arifin, Muhammad Syamsul; Subroto, Dewi Intan Galih; Setiyadi, Alif Cahya; Fata, Khoirul (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study investigates grammatical errors in Arabic reading among final-year students at Baitul Arqom Islamic Boarding School. Using a qualitative approach with a descriptive-linguistic design, this research aims to identify the types of grammatical errors and explain their causes in accordance with the grammatical rules of an-Nahwu al-Wāḍih by al-Jarim and Amin. The subjects of this study were 46 final-year female students selected through a total sampling method. The data consisted of students’ Arabic reading performances, recorded and annotated with identified grammatical errors, supported by questionnaires and grammatical references. Data were analyzed using the distributional (agih) method, which involved identifying error positions, classifying them according to Arabic sentence structure, and providing linguistic descriptions and evaluations of the errors. The findings show that students make several grammatical errors related to Arabic sentence structure, particularly in maf‘ūl bih, fā‘il, na‘t, and fi’il madhī. These errors primarily stem from weak foundational grammar, lack of focus during reading, and reliance on guessing case endings. The study concludes by stressing the need to strengthen grammatical understanding through practical reading activities, immediate correction during performance, and exposure to diverse texts that develop students’ awareness of Arabic sentence structure.